Organization and content of primary care for adolescents – comparison of actual and desired situation. (13th November 2019) - Jansen, D E M C; Visser, A; Vervoort, J P M; Kocken, P; Reijneveld, S A; Blair, M; Alexander, D; Rigby, M; Michaud, P A
Abstract: To successfully navigate increasing autonomy, independence and health behaviors in adolescence, accessible adolescent health care services (AHS) are essential. AHS comprise all services in primary care that are aimed at the specific needs of adolescents and can be provided in various settings such as public services, private services, schools and hospitals. In the MOCHA project (Models of Child Health Appraised) we assessed the structure and content of AHS in 30 European countries against the standards in the field of adolescent health services: accessibility, staff attitude, communication, staff competency and skills, confidential and continuous care, age appropriate environment, involvement in health care, equity and respect and a strong link with the community. The results revealed that although half of the 30 countries did adopt adolescent-specific policies, many countries did not meet the current standards of quality health care for adolescents. For example, the ability to provide emergency mental health care is limited. In addition, one third of the countries do not have a formal policy which guarantees the confidentiality of a consult and the possibility to consult a physician without parents knowing. Finally, around half of the countries do not have specialized centers in adolescent health care in order to tackle comprehensive health issues. Access to adolescent health care services needs to be improved for vulnerable adolescents such as migrant adolescents. Schools, ambulatory settings and hospitals should offer accessible, comprehensive health care and a culturally appropriate approach, particularly given the number of migrant adolescents living in EU and EEA countries. Finally, the health care systems should improve their communication strategies, to assist young people in understanding their rights and responsibility in the domain of health, and how and where to access to adequate care.